2015
DOI: 10.3892/or.2015.3962
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a inhibits the migration and invasion of esophageal squamous cell carcinoma by targeting Yin Yang-1

Abstract: Esophageal squamous cell carcinoma (ESCC), one of the most common gastrointestinal tumors, is known for its high mortality rate. microRNAs (miRNAs) have been reported to play important regulatory roles in cancer metastasis and progression. miR-34a has been demonstrated to be associated with the development of and metastasis in certain types of cancer via various target genes, but its function and targets in ESCC are unknown. The aim of this study was to examine whether the expression of miR-34a was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 33 publications
4
25
1
Order By: Relevance
“…Deregulated miRNAs have an important role in many malignancies which have recently been identified as oncomir or tumor suppressor in many cancers [21][22][23]. ESCC is one of these malignancies in which altered miRNAs expression has been reported [24,52,53].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Deregulated miRNAs have an important role in many malignancies which have recently been identified as oncomir or tumor suppressor in many cancers [21][22][23]. ESCC is one of these malignancies in which altered miRNAs expression has been reported [24,52,53].…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have reported the potential clinical roles of miRNAs in several diseases such as breast cancer [15], cervical cancer [16], colorectal cancer [17], gastric cancer [18], bladder cancer [19], lung cancers [20], etc., in which altered expression patterns of miRNAs have been shown to act in the oncogenic or tumor suppressor pathways [21][22][23]. Furthermore, altered miRNA expression has been reported in esophageal cancers [24][25][26].…”
Section: Introductionmentioning
confidence: 98%
“…Wild type p53 induces the transcription of miR-34a which targets several molecules that are involved in cellular transformation and carcinogenesis [2729]. The abnormal miR-34a expression has been revealed in breast cancer [31], colon cancer [32], cervical cancer [33], prostate cancer [34], esophageal squamous cell carcinoma [37], and lung cancer [38]. MiR-34a may act on its target genes to regulate the proliferation, apoptosis, invasion, metastasis and epithelial mesenchymal transition of cancer cells, exert inhibitory effects on the growth and metastasis of cancers [39].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated expression of miR-34a-controlled genes may occur due to mutations that inactivate p53 in tumor cells (Balca-Silva et al, 2012). Recently, Nie et al (2015) found that miR-34a was downregulated in ESCC tissues compared with that in normal tissues (P < 0.05), and that miR-34a overexpression increased apoptosis and decreased clonogenic formation, whereas it inhibited invasion and migration of ESCC cells by suppressing MMP-2 and -9 expression. However, the clinical significance and prognostic value of miR-34a in ESCC had not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%